Analisis Kinerja Bank Pada Pt. Bank Danamon Indonesia Tbk Dengan Metode Camel - Alvia, Nurul; Nasution, Anggi Pratama (Jurnal Riset Akuntansi dan Bisnis, 2024)
This research discusses the important role of banks in reviving a country's economy, focusing on analysis of bank performance. Banks not only act as fundraisers and credit distributors, but also have a vital role in maintaining the stability of the country's economic system. This study uses the CAMEL method to evaluate bank health, with PT Bank Danamon Indonesia Tbk as the object of study. Data was obtained from Bank Danamon's financial statements from 2016 to 2021, and the analysis was carried out using CAMEL formulas. The results showed that Bank Danamon Indonesia obtained different credit predicates in the management aspect, but overall it was categorized as a healthy bank.